Complex Reactive Acids from Methanol and Carbon Dioxide Ice: Glycolic Acid (HOCH2COOH) and Carbonic Acid Monomethyl Ester (CH3OCOOH) - Joshua H. Marks; Jia Wang; Mikhail M. Evseev; Oleg V. Kuznetsov; Ivan O. Antonov; Ralf I. Kaiser (The Astrophysical Journal, 2023)
The formation of complex organic molecules by simulated secondary electrons generated in the track of galactic cosmic rays was investigated in interstellar ice analogs composed of methanol and carbon dioxide. The processed ices were subjected to temperature-programmed desorption to mimic the transition of a cold molecular cloud to a warmer star-forming region. Reaction products were detected as they sublime using photoionization reflectron time-of-flight mass spectrometry. By employing isotopic labeling, tunable photoionization and computed adiabatic ionization energies isomers of C _2 H _4 O _3 were investigated. Product molecules carbonic acid monomethyl ester (CH _3 OCOOH) and glycolic acid (HOCH _2 COOH) were identified. The abundance of the reactants detected in analog interstellar ices and the low irradiation dose necessary to form these products indicates that these molecules are exemplary candidates for interstellar detection. Molecules sharing a tautomeric relationship with glycolic acid, dihydroxyacetaldehyde ((OH) _2 CCHO), and the enol ethenetriol (HOCHC(OH) _2 ), were not found to form despite ices being subjected to conditions that have successfully produced tautomerization in other ice analog systems.